Cover Picture: Biotechnology Journal 11/2019. Issue 11 (3rd November 2019) - Wang, Xiaojie; Deng, Zixin; Liu, Tiangang
Abstract : Glucose isomerases are important industrial enzymes to produce highfructose corn syrup (HFCS) which is sweetener and widely used in beverages and foods. The gene of glucose isomerase from Streptomyces rubiginosus is overexpressed under the control of strong promoter (rRNA promoter) which integrated on the chromosome as marker‐free form, so the high efficiency and high stability of Streptomyces strain for glucose isomerase is achieved. This is reported by Xiaojie Wang, Zixin Deng, and Tiangang Liu in article 1900114 .